Development of E-Worksheet with Guided Discovery for Slow Learners - Poniyati, Poniyati; Andriyani, Andriyani; Setyawan, Fariz (Universitas Ahmad Dahlan, 2024)
Inclusive education was advocated as an education service system where students with special needs were required to study in nearby schools, participating in regular classes alongside their peers. Slow learner students were thus allowed to study at regular schools and were provided with the same learning materials as other regular students, based on the existing curriculum content. One of the materials studied was SPLDV material. SPLDV was identified as one of the materials that proved difficult for slow learners to understand and learn. This was because SPLDV material discussed contextual problems in their solutions, requiring understanding, logical reasoning, and coherent steps for solving. Consequently, solving SPLDV contextual problems required critical thinking skills. The study aimed to produce E-Worksheet based on Guided Discovery Learning that was valid and practical for improving slow learner students' critical thinking skills in SPLDV material. The research followed the ADDIE development stage (Analysis, Design, Development, Implementation, and Evaluation) and focused on grade VIII slow learner students at SMP Muhammadiyah 1 Pundong. Instruments included material expert validation sheet instruments, media expert validation sheet instruments, and student response questionnaires. Validation scores met